Criticality and strong intermittency in the Lorentz Channel - Karlis, Alexandros Konstantinos; Diakonos, Fotis K.; Petri, Christoph; Schmelcher, Peter (Physical review letters, 2012)
We demonstrate the emergence of criticality due to power-law cross correlations in an ensemble of noninteracting particles propagating in an infinite Lorentz channel. The origin of these interparticle long-range correlations is the intermittent dynamics associated with the ballistic corridors in the single particle phase space. This behavior persists dynamically, even in the presence of external driving, provided that the billiard’s horizon becomes infinite at certain times. For the driven system, we show that Fermi acceleration permits the synchronization of the particle motion with the periodic appearance of the ballistic corridors. The particle ensemble then acquires characteristics of self-organization as the weight of the phase space regions leading to critical behavior increases with time.
Published 11 September 2012 (online)
Gesehen am 27.06.2018